Strengthening Legal Safeguards for Indonesian Migrant Workers Against Human Trafficking - Sukman; Budi Parmono; Rahmatul Hidayati (APPTHI, 2025)
Legal protection for Indonesian Migrant Workers plays an important role in efforts to combat human trafficking, which is still a serious problem in the world. This study examines various regulations related to Indonesian Migrant Worker policies and criminal sanctions for perpetrators of human trafficking. This study uses a normative legal method by examining various sources of law, both national law and international agreements such as the Palermo Protocol. The results of the study show that Indonesia has ratified various major international conventions and has passed Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers and Law Number 21 of 2007 concerning the Eradication of Human Trafficking. These laws provide strong protection for migrant workers from the conservation, placement, and post-placement stages, and provide severe penalties for perpetrators of human trafficking. However, despite these various legal efforts, there are still many problems in law enforcement. This is reflected in the increasing cases of Human Trafficking, with 2,149 victims rescued in 2023. The study highlights the urgent need for better oversight, stricter conservation rules, and stronger law enforcement to prevent, cover and protect migrant workers.